1993
DOI: 10.1093/ajcn/57.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ascorbic acid concentrations relate inversely to blood pressure in human subjects

Abstract: This study relates antioxidant status and blood pressure (BP) in 168 healthy residents of Augusta, GA, following usual diets. BP ranges were systolic (S) 84-152, mean 112 +/- 1 mm Hg, and diastolic (D) 52-96, mean 72 +/- 1 mm Hg. Plasma concentrations of ascorbic acid (AA) were significantly inversely related to SBP (r = -0.18, P < 0.05) and DBP (r = -0.20, P < 0.01); with regression equations SBP vs AA = -0.083C + 116 and DBP = -0.077C + 76. Highest and lowest quintiles of AA differed significantly in mean SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 20 publications
0
44
0
3
Order By: Relevance
“…Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes (240), but had no effect in postmenopausal women or in healthy subjects (140). Population studies have demonstrated an inverse association between plasma vitamin C levels and vitamin C consumption with blood pressure (28,139), and a recent meta-analysis reported that vitamin C supplementation reduced systolic and diastolic blood pressure (147). In patients with white coat hypertension, serum protein carbonyl (indicating protein oxidation) was increased and endogenous antioxidant proteins (protein thiol, SOD, glutathione) were decreased compared with normotensive individuals, further supporting a relationship between low antioxidant capacity, increased oxidative stress, and hypertension (201).…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%
“…Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes (240), but had no effect in postmenopausal women or in healthy subjects (140). Population studies have demonstrated an inverse association between plasma vitamin C levels and vitamin C consumption with blood pressure (28,139), and a recent meta-analysis reported that vitamin C supplementation reduced systolic and diastolic blood pressure (147). In patients with white coat hypertension, serum protein carbonyl (indicating protein oxidation) was increased and endogenous antioxidant proteins (protein thiol, SOD, glutathione) were decreased compared with normotensive individuals, further supporting a relationship between low antioxidant capacity, increased oxidative stress, and hypertension (201).…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%
“…(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996) using the search terms 'blood pressure' and 'ascorbic acid'. This was complemented by a Eleven studies 18,22,[25][26][27]30,[32][33][34][35][36] reported on the association between blood levels of vitamin C and search of personal bibliographic files, books and relevant reviews, 7,8,12,13 and follow-up of citations in BP in 14 populations. In 10 of these 14 populations a significant inverse association was reported, but in references already located.…”
Section: Laboratory Studies and Animal Experiments Suggestmentioning
confidence: 99%
“…In 10 of these 14 populations a significant inverse association was reported, but in references already located. We continued the process of cross-referencing until no new references only four 27,[30][31][32][33][34]36 was it possible to estimate directly the difference in BP for a 50 mol/L difference in were identified. These searches were not restricted to English language journals but all the articles plasma ascorbic acid.…”
Section: Laboratory Studies and Animal Experiments Suggestmentioning
confidence: 99%
“…33 In addition, it can regenerate vitamin E from the radical form. 45 A number of epidemiological studies have shown a negative correlation between BP and vitamin C. [57][58][59][60] Several mechanisms by which vitamin C might influence BP have been proposed, 60 including a free radicalscavenging property preventing prostacyclin synthetase inhibition. 58 Moreover, it has also been suggested that BP may influence vitamin C metabolism.…”
Section: Discussionmentioning
confidence: 99%